An Intensive Educational Intervention Significantly Improves the Adoption of Single Fractionation Radiotherapy in Uncomplicated Bone Metastases. (July 2021) - Donati, Costanza M.; Nardi, Elena; Galietta, Erika; Alfieri, Maria L.; Siepe, Giambattista; Zamagni, Alice; Buwenge, Milly; Macchia, Gabriella; Deodato, Francesco; Cilla, Savino; Strigari, Lidia; Cammelli, Silvia; et al.
Introduction: An education strategy was employed in our department to increase the rate of patients with uncomplicated painful bone metastases undergoing single fractionation radiotherapy (SFRT). The purpose of this report is to analyze the results of this strategy over a 5 year period. Materials and Methods: In January 2015, two meetings were organized in our department. In the first, data from an audit on the current SFRT rate were shown. In the second, evidence of SFRT efficacy in the relief of pain from uncomplicated bone metastases was presented. In addition, during the weekly discussion of clinical cases, the opportunity to use the SFRT was systematically recalled. Using our institutional database, all patients treated with radiotherapy for uncomplicated painful bone metastases in the period between 2014 (year considered as a reference) and 2019 were retrieved. Data regarding treatment date (year), radiotherapy fractionation, and tumor, patients, and radiation oncologists characteristics were collected. Results: A total of 627 patients were included in the analysis. The rate of patients undergoing SFRT increased from 4.0% in 2014 to 63.5% in 2019 ( p < 0.001). At multivariable analysis, the delivery of SFRT was significantly correlated with older patients age (>80 years), lung cancer as the primary tumor, treatment prescribed by a radiation oncologist dedicated to palliative treatments, and treatment date (2014 vs 2015–2019). Conclusions: This retrospective single-center analysis showed that a simple but intensive and prolonged departmental education strategy can increase the rate of patients treated with SFRT by nearly 16 times.